Strategi Finansial Islam Dalam Mewujudkan Maslahat Ekonomi - Syafrina Yuni Lubis; Patma Wati; Marliyah (Institut Muslim Cendekia, 2023)
Since the emergence of the global financial crisis recently, the financial system requires changes that must be appropriate. In the economic sector, financial institutions do have an important role to play in influencing the stability of a country’s economy experience from the crisis shows that without good financial system resilience, the process of economic development will not be able to achieve economy stability which will ultimately create prosperity. The Islamic economic system is definitely able to answer the challenges of Islamic finance because it is sourcesd from syara’ and the paradigm of Islamic finance which puts forward sharia maqasid so as to create prosperity. The goals of the Islamic financial system are also often stated in commendable terms such as increasing economic welfare, poverty alleviation to fulfilling basic human needs. This research is a library research is a qualitative descriptive study with a phenomenological approach. This research is a library research that uses secondary data obtained through scientific articles and other relevant documents. The Islamic financial system is increasingly experiencing significant developments from year to year. This can be seen from the many institutions that stand by sharia principles. In practice, Islamic finance is also considered capable of answering questions about the development of the conventional financial sector. The presence of the Islamic financial system is a breath of fresh air whose precense brings moral values to all human beings as a whole. In addition, the Islamic financial system in the world has also begun to become the subject of study by economic experts. This can be seen from the many foreign countries that have begun to develop sharia-based financial institutions